Short-term application of chicken manure under different nitrogen rates alters structure and co-occurrence pattern but not diversity of soil microbial community in wheat field - Jin, Haiyang; Zhang, Deqi; Yan, Yaqian; Yang, Cheng; Fang, Baoting; Li, Xiangdong; Shao, Yunhui; Wang, Hanfang; Yue, Junqin; Wang, Yanjing; Cheng, Hongjian; Shi, Yanhua; et al. (Frontiers in Microbiology, 2022)
Manure application is an effective way to improve the utilization efficiency of organic resources and alleviate the adverse effects of long-term application of chemical fertilizers. However, the impact of applying manure under different nitrogen rates on soil microbial community in wheat field remains unclear. Treatments with and without chicken manure application under three nitrogen rates (N 135, 180 and 225 kg·hm-2) were set in wheat field. Soil organic carbon, available nutrients, and abundance, diversity, structure and co-occurrence pattern of soil microbial community at wheat maturity were investigated. Compared with no manure application, chicken manure application increased the soil organic carbon and available phosphorus, while the effects on soil mineral nitrogen and available potassium varied with different nitrogen rates. Chicken manure application significantly increased soil bacterial abundance under the nitrogen fertilization of 135 and 225 kg·hm-2, increased soil fungal abundance under the nitrogen fertilization of 135 kg·hm-2, but decreased soil fungal abundance under the nitrogen fertilization of 180 and 225 kg·hm-2 (P<0.05). There was no significant difference in alpha diversity indices of soil microbial communities between treatments with and without chicken manure application under different nitrogen rates (P>0.05). Chicken manure application and its interaction with nitrogen rate significantly changed soil bacterial and fungal community structures (P<0.05). There were significantly different taxa of soil microbial communities between treatments with and without chicken manure application. Chicken manure application reduced the ecological network complexity of soil bacterial community and increased that of soil fungal community. In summary, the responses of soil available nutrients and microbial abundance to applying chicken manure varied with different nitrogen rates. One growing season application of chicken manure was sufficient to alter the soil microbial community structure, composition and co-occurrence pattern, whereas not significantly affected soil microbial community diversity.